LABORATORY INSTRUCTIONAL MODEL TO ENHANCE THINKING SKILL OF FUTURE PROBLEM SOLVING FOR HOME ECONOMICS STUDENTS - เครือเมฆ, โสรฌา; ตัณฑวุฑโฒ, วิกร; รังสยาธร, ชีพสุมน (Phranakhon Rajabhat Research Journal : Humanities and Social Sciences, 2018)
The purposes of this research were: 1) to develop a laboratory instructional model to enhance future problem solving thinking skill for home economics students, and 2) to evaluate the effectiveness of the developed instructional model. The research was divided into three phases: 1) A study of theory and home economics laboratory learning management; 2)Development of an instructional model; and 3) Testing the developed instructional model which was evaluated by 6 experts, subjects consisted of 37 third year students home economics program, Phranakhon Rajabhat University, who enrolled in International Food course. The research instruments included an achievement test, a future problem solving evaluation form, a performance evaluation form and a questionnaire of satisfaction towards the instructional model. The research data were statistically analyzed using the mean, standard deviation and t-test for dependent samples. The results of this study were as follows: 1. The developed instructional model consisted of 5 elements: 1) principles; 2) objectives; 3) instructional model which consisted of four learning steps, that is, theory reviewing, planning and thinking with future problem solving, experiencing, evaluating and problem reflecting; 4)the condition to use the model; and 5) the measurement and evaluation. 2. The evaluation results in a field try-out showed that the developed instructional model was able to use as learning activity. The students’ post-learning results of achievement and future problem solving thinking skill were significantly higher scores than their pre-learning at .01 level, performance skill was at good level and students indicated most satisfaction towards the instructional model ( = 4.52, S.D.=0.41).